Hsa_circ_0000515 is a novel circular RNA implicated in the development of breast cancer through its regulation of the microRNA‐296‐5p/CXCL10 axis - Cai, Fenglin; Fu, Wenjie; Tang, Lei; Tang, Jinhai; Sun, Jinming; Fu, Guangshun; Ye, Gang (The FEBS journal, 2021)
Cancer metastasis is a major cause of death among women afflicted with breast cancer (BC) and understanding the molecular processes involved is a major focus in BC research. Circular RNAs (circRNAs) have emerged as genomic regulatory molecules in carcinogenesis and metastasis; however, their role in BC is unclear. We characterized a novel circRNA, hsa_circ_0000515, in context of BC. We collected 340 cancerous tissues surgically resected from BC patients and found hsa_circ_0000515 was upregulated in BC tissues and associated with poor prognosis of BC. Silencing of hsa_circ_0000515 impaired cell cycle progression, cell proliferation, and invasion, attenuated inflammatory response, and reduced the proangiogenetic potential of BC cells. RNA pull‐down and dual‐luciferase reporter gene assays showed that hsa_circ_0000515 binds miR‐296‐5p, preventing it from repressing CXCL10 expression. We also observed that miR‐296‐5p inhibition or CXCL10 overexpression promoted cell cycle progression, restored proliferative, invasive and proangiogenetic abilities, and increased inflammatory response in MCF‐7 cells in the absence of hsa_circ_0000515. In vivo analyses showed that partial loss of hsa_circ_0000515 reduced the tumor growth of MCF‐7 cells in nude mice. The key findings from this study revealed that targeting hsa_circ_0000515 might be an effective strategy to combat BC. Hsa_circ_0000515 impairs miRNA‐296‐5p‐mediated CXCL10 inhibition to promote cell proliferation, angiogenesis, and inflammation in BC cells. Hsa_circ_0000515 is highly expressed in BC cells. Hsa_circ_0000515 can competitively bind to miR‐296‐5p and then impair the binding of miR‐296‐5p to CXCL10 to upregulate CXCL10 expression, thereby stimulating the proliferative and invasive properties of BC cells and potentiating angiogenesis and inflammation.